2010
DOI: 10.1186/1752-0509-4-107
|View full text |Cite
|
Sign up to set email alerts
|

Integrative multicellular biological modeling: a case study of 3D epidermal development using GPU algorithms

Abstract: Background: Simulation of sophisticated biological models requires considerable computational power. These models typically integrate together numerous biological phenomena such as spatially-explicit heterogeneous cells, cell-cell interactions, cell-environment interactions and intracellular gene networks. The recent advent of programming for graphical processing units (GPU) opens up the possibility of developing more integrative, detailed and predictive biological models while at the same time decreasing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 78 publications
0
70
0
Order By: Relevance
“…A similar approach has been taken to describe the role of Myosin II patterning in driving intercalation during germband extension (80). Such biological detail is rarer in the more complex mechanocellular models described above; though recent examples include (44,69). Further development of increasingly detailed mechanocellular models will require the careful derivation of key relationships between the fluorescence intensity of relevant proteins and mechanical properties from liveimaging datasets.…”
Section: Incorporating Signallingmentioning
confidence: 99%
“…A similar approach has been taken to describe the role of Myosin II patterning in driving intercalation during germband extension (80). Such biological detail is rarer in the more complex mechanocellular models described above; though recent examples include (44,69). Further development of increasingly detailed mechanocellular models will require the careful derivation of key relationships between the fluorescence intensity of relevant proteins and mechanical properties from liveimaging datasets.…”
Section: Incorporating Signallingmentioning
confidence: 99%
“…The inter-cellular interaction described by the second term takes all pair-interactions between the elements β j of other cells j and the elements α i of cell i into account. Numerically, the forward Euler and a two-step Runge-Kutta scheme have been used to integrate Equation (11) [92]. Similar to the inter-atomic interaction potentials in molecular dynamics simulations, the phenomenological potentials V intra , V inter are chosen such that the subcellular elements prefer to be in an equilibrium distance to their neighbouring elements, i.e., that the subcellular elements repel each other when the distance between two cells is low, and attract each other when the distance is large.…”
Section: Subcellular Element Modelsmentioning
confidence: 99%
“…However, due to its algorithmic simplicity borrowed from molecular dynamics, efficient library implementations can be used [92,93]. It has been reported that the SEM is suitable to study problems with up to 10,000 cells [91].…”
Section: Subcellular Element Modelsmentioning
confidence: 99%
“…However, most of these ABMs have been focused on delineating intracellular detail as an adjunct to basic research. [24][25][26][27] We propose that ABMs are also well suited to a translational role to bridge basic science knowledge and the rational development of clinically applicable strategies. 14,23,28,29 We have developed a series of ABMs with this specific goal in mind.…”
Section: Equation-based Models Of Inflammation and Wound Healingmentioning
confidence: 99%